A new species of Eriocaulon (Eriocaulaceae) from Northeast India, the first report of a cormous Eriocaulon from India - A., Vahidha Parveen; Nampy, Santhosh; V.k., Lulu Mumthas; K.p., Vaishnavi; Balakrishnan, Archana; K., Arshad (Phytotaxa, 2026)
A new species, Eriocaulon meghalayense V.Parveen & Nampy, is described from the East Khasi Hills, Meghalaya, Northeast India. It is most similar to E. cherrapunjianum but differs in possessing a distinct corm and other traits. It also resembles the cormous species E. cormosum and E. xenopodion, yet can be distinguished by its scapes and seed characteristics. A detailed description, photographs, scanning electron micrographs of the seeds, and a comparison of the key diagnostic characters with allied species are provided. The species is known only from a single locality and is provisionally assessed as Data Deficient (DD).